The possibility of Chlorella vulgaris green algae culture in secondary treated wastewater - ديب, جورج; بكداش, علي (Latakia University Journal -Biological Sciences Series, 2020)
Abundance has been studied Green algae growth in secondary treated wastewater and changes in pH values, healthy at different lighting spells (light shift 24 light / 0 dark, light shift 16 light / 8 dark, light 8 light / 16 dark) compared to the liquid culture medium Chu-10. The average number of cells in secondary treated wastewater at a light spell was 24 light / 0 darkness 1370972.40 and at a light spell 16 light / 8 darkness, the average number of cells was 168,2596, while record 1403757.80 at light shift 8 light / 16 darkness, and the highest number of algae cells was 2919934 cells / At a light fit, ml was 16 light / 8 dark, and the value of pH was decreased as the number of cells increased.